Curious George. Goes green - Universal Studios Home Entertainment (Firm); PBS for Kids. ([United States] : Universal Studios Home Entertainment, 2009)
Curious George is back, exploring new things like recycling, gardening, and helping the environment. As always, he can use a little help from his friends, including the Man with the Yellow Hat. Time to set a course for adventure with eight new shows.
The perfect carrot -- Everything old is new again - Curious George and the trash -- Much ado about nothing -- George digs worms -- Seed trouble -- Ice Station Monday -- Shipwrecked with Hundley.
Title from disc surface.
Fullscreen.
Originally broadcast on television as 8 individual episodes.
Not rated.
Subtitles for the deaf and hard of hearing (SDH).
Keywords: Curious George -- (Fictitious character) -- Juvenile drama; Monkeys -- Juvenile drama; Sustainable living -- Juvenile drama; Recycling (Waste, etc.) -- Juvenile drama; Gardening -- Juvenile drama; Animated television programs; Children's television programs; Television programs for the hearing impaired